Hubungan Lama Paparan Polutan Udara Dengan Saturasi Oksigen Pada Karyawan SPBU Di Wilayah Kabupaten Blitar - Alkhalifa Amin (Jurnal Keperawatan Terapan, 2018)
Exposure to air pollutants (benzene) in the SPBU environment is very influential to oxygen saturation, especially operators on filling point. The purpose of this study is to determine the relationship between the duration of exposure to air pollutants with oxygen saturation in SPBU employees in Blitar district. Design in this research is analytic correlation with Cross Sectional approach. The population of all employees of filling stations amounted to 43, the sample used amounted to 30 by purposive sampling technique. The results of the analysis using Spearman test. The results showed that oxygen saturation in gas station employees worked more than 6 months to less than 5 years, normal oxygen saturation (57%), mild hypoxia (7%), and moderate hypoxia (3%). For gas station employees who work between 5 years to 10 years, normal oxygen saturation (10%) and those with mild hypoxia (3%). And for SPBU employees who work more than 10 years of normal oxygen saturation (10%), who have mild hypoxia (7%), and those with moderate hypoxia (3%). The conclusion of this study there is a relationship between long exposure to air pollutants with oxygen saturation at SPBU employees in Blitar District with p value is 0,033. Recommendations for subsequent researchers to conduct research by using blood gas analysis.